Multivariables Determining Earnings per Share within the U.S. Medical Laboratories & Research Industry - Vedd, Rishma; Lazarony, Paul; Yassinski, Nataliya (Archives of Business Research, 2014)
The objective of this study is to examine the key variables determining earnings per share for the Research Industry. In this study financial statements for ten years (from 2003 to 2012) of the publicly listed leading U.S. companies in the Medical Laboratories and Research Industry based on their size are gathered. In making proper decisions, we need to take into consideration such indicators as financial ratios, operating cash flows, and firm size. Since all of these factors indicate different aspects of the company’s performance, each of those variables alone may not give the investor a complete and consistent estimate of the earning per share of a specific stock. Therefore, a multivariable regression analysis on the effect of firm size, financial ratios, and operating cash flows on earnings per share and the regression model used to predict the future earnings per share are utilized here. The objective is to analyze any significant relationships between those indicators and the earnings per share. The result indicates that the debt ratio, present value to book value ratio, and operating cash flow ratio have no significant relationship with earnings per share. The most significant predictors of earnings per share are the firm size, net profit margin ratio, return on equity ratio, current ratio, and total assets turnover ratio. Keywords: Financial ratios, Earning per Share, U.S. market, Firm size, Cash Flow